Miniature Mimesis of Heritage As a New Visual Communication Media of Architecture Case Study: The Complex of the Kasunanan Kingdom - P,ST, MT, Dyah.S.Pradnya. (KnE Social Sciences, 2019)
Ancient building complexes, also known as tangible heritage assets, have been published on various social media platforms, generating interest from academics, governments and investors. The tourism industry then becomes the main explorer of these potential assets. Various job opportunities and the potential for artwork creation also develop out of the discovery. All of these appear to generate benefits and financial gain. However, losses are rarely anticipated surrounding the damage of tangible heritage assets and local customs and privacy. The development of tourism and growing interest in heritage sites can cause degradation to heritage objects and dramatic changes to the local society. Based on these conditions, the researcher was interested to explore this phenomenon and understand the dynamics of new heritage sites. The research was conducted using the qualitative naturalistic method for 3 months. Observation and data collection was done by purposive sampling, snowball sampling and also a cross-sectional system. While resource people and informants in the case study were found according to the research theme. The results of the research were (1) Reconstruction efforts are more focused on preservation so as to control and limit commercialization; (2) Providing limits on public, semi-public, semi-private and private areas through miniature mimesis of heritage, which serves to provide adaptive experiences in certain. locations; (3) Restoring natural living space contaminated by tourism activities so indigenous peoples can have the right to continue living within the space. Keywords: heritage, lifestyle, maquette, mimesis, damage